ELECTRO-PHOTONIC EMISSION ANALYSIS AND HARDWARE-SOFTWARE RECORDING OF HEART RATE VARIABILITY DURING AN OBJECTIVE STRUCTURED CLINICAL EXAMINATION - Nevoit, G.V.; Potiazhenko М.М.; Mintser О.P.; Babintseva, L.Yu. (World of Medicine and Biology, 2020)
Practical issues of studying the role of electromagnetic phenomena of cardiac activity and tissues of the human body in the diagnosis of the functional state of the human body are presented in the article. The purpose of the publication is to determine the clinical diagnostic potential and feasibility of using computerized techniques for a short recording of Heart Rate Variability and Electro-Photonic Emission Analysis as part of the instrumental component of an Objective Structured Clinical Examination in the clinic of Internal Medicine. The results of the examination of functionally healthy people and compensated patients with Noncommunicable Diseases are presented in the article.